Expansion of C1Q Genes in Zhikong Scallop and Their Expression Profiling After Exposure to the Toxic Dinoflagellates - Xu, Kexin; Wang, Yinghui; Lian, Shanshan; Hu, Naina; Chen, Xiaomei; Dai, Xiaoting; Zhang, Lingling; Wang, Shi; Hu, Jingjie; Hu, Xiaoli; Bao, Zhenmin (Frontiers in Marine Science, 2021)
C1Q (Complement 1Q) is an important recognition molecule in immunological complement system, which was also been reported could be putatively involved in the stress responses induced by endotoxins or exotoxins, potentially through detoxification processes. Marine bivalves are well adapted to highly complex aquatic environments with various stressors. As filter feeders, they have to in cope with highly potent microalgae-derived neurotoxin, such as paralytic shellfish toxin (PSTs). Zhikong scallops, Chlamys farreri, are commercially important bivalve with remarkable ability to accumulate PSTs. Exploring the C1Qs related to PST accumulation in C. farreri could benefit our understanding about the adaptations of bivalve species. In the present study, we systematically analyzed C1Q genes in C. farreri. In total, 97 CfC1Q genes that mainly from the expanded C1Q-B subfamily were identified, from which the C1QL, C1QTNF, C1QDC1 members in C. farreri were revealed to be under positive selection. Spatiotemporal expression analysis revealed that most CfC1QLs and CfC1QDC1s were highly expressed during the post-umbo stage and in hepatopancreas, while most CfC1QTNF members were highly expressed after creeping larva stage and in mantle. The hepatopancreas and kidney in C. farreri are two toxin-rich organs with the highest concentrations of PSTs, acting as major “centers” for toxin accumulation and transformation, respectively. Therefore, after feeding the scallops with PST-producing dinoflagellates Alexandrium minutum and Alexandrium catenella, we determined the expression patterns of CfC1Qs in these two organs. In kidney, more than 85% of CfC1QLs and CfC1QDC1s showed drastic up-regulation with both diets. However, among these members with significant induction, different response manner was detected after feeding with A. minutum and A. catenella, respectively as acute and chronic response patterns. In comparison, far more less CfC1Qs showing significantly up-regulation in hepatopancreas with both toxic diets and only mild regulation pattern could be found. These organ-, toxin-, and time-dependent genetic regulation of CfC1Qs may attribute to the virulence difference on account of the tissue-specific or dinoflagellate-specific different toxin analogs composition, implying the possible involvement of CfC1Qs in PST transport and homeostasis.